An intriguing instance of type 2 lepra reaction-induced granulomatous rhinosinusitis: a case report - Rajan, Surya; Chilakamarri, Srivalli; Chockalingam, Satish Kumar; Ramesh Colbert, Kumaran (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Hansen disease, or leprosy, is a granulomatous disease caused by the bacteria Mycobacterium leprae, which is endemic worldwide. The upper respiratory tract is the main portal of entry for bacilli, and the paranasal sinuses serve as a reservoir of infection and may exhibit features of rhinosinusitis. We presented a man who manifested features of acute rhinosinusitis not respond to standard therapies incidentally found to have type II lepra reaction and showed miraculous recovery of symptoms following oral steroids and patient on close follow-up. Although leprosy has been declared eliminated globally in most countries, otorhinolaryngologists should still consider type II lepra reactions a differential diagnosis whenever a patient presents with nasal symptoms that do not respond to standard therapies.